PENGABDIAN KEPADA MASYARAKAT MELALUI KULIAH KERJA NYATA (KKN) DI DESA BAKALANPULE KABUPATEN LAMONGAN - Muhammad Elva Nur Fariz; Darianto; Bayu Malikhul Askhar; Didik Puji Wahyono; Arian Yusuf Wicaksono (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Community service through Real Work Lectures (KKN) is a form of student contribution in overcoming problems that exist in society. This study aims to examine the role of KKN in increasing environmental awareness and providing education to children in Bakalanpule Village, Lamongan Regency. The method used in this research is observation. KKN students participate in environmental cleaning activities, counseling about the importance of maintaining cleanliness, and educating children about the importance of protecting the environment. The results showed that through KKN, environmental awareness in Bakalanpule Villagenexperienced a significant increase. People are starting to understand how important it is to keep clean and take care of the environment around them. The children also showed increased knowledge about the importance of protecting the environment through educational activities conducted by KKN students.